2010
DOI: 10.1155/2011/739751
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of VKORC1 and CYP4F2 Genes Related to Warfarin Maintenance Dose in Patients with Myocardial Infarction

Abstract: The aim of this study was to investigate whether the VKORC1*3 (rs7294/9041 G > A), VKORC1*4 (rs17708472/6009 C > T), and CYP4F2 (rs2108622/1347 C > T) polymorphisms were associated with elevated warfarin maintenance dose requirements in patients with myocardial infarction (n = 105) from the Warfarin Aspirin Reinfarction Study (WARIS-II). We found significant associations between elevated warfarin dose requirements and VKORC1*3 and VKORC1*4 polymorphisms (P = .001 and P = .004, resp.), whereas CYP4F2 (1347 C > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…This observation is in line with a previous finding that CYP4F2*3 has only a small effect on warfarin dose variability [23]. However, the effect of CYP4F2*3 on warfarin dose-response variability is debatable; in fact, it ranges from 1%–7% [23], [33], [34] to not significant [26], [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is in line with a previous finding that CYP4F2*3 has only a small effect on warfarin dose variability [23]. However, the effect of CYP4F2*3 on warfarin dose-response variability is debatable; in fact, it ranges from 1%–7% [23], [33], [34] to not significant [26], [27].…”
Section: Discussionsupporting
confidence: 92%
“…Subjects bearing polymorphisms in one or both of these genes require lower or higher warfarin doses than subjects bearing the wild-type genes to obtain an adequate anticoagulant effect [1], [8], [16], [19][22]. More recently, patients bearing a SNP (rs2108622) in the CYP4F2 gene (Gene Bank Accession Number AF22194; chr.19p13.12), which is the vitamin K 1 oxidase involved in vitamin K 1 metabolism, were found to require a warfarin dose slightly higher than normal [23][25] or similar to normal [26], [27]. Moreover, a meta-analysis revealed a statistically significant association between rs2108622 and the interindividual warfarin dose variation [28], [29].…”
Section: Introductionmentioning
confidence: 99%
“…5,6,1520,2533,3540,42 for these studies, we performed a separate meta-analysis stratified by gender and exploratory meta-analyses to evaluate the association between polymorphisms of VKORC1 and CYP2C9 and coumarin maintenance dose in the same populations that had been genotyped for the CYP4F2 variant, as well as the impact of the CYP4F2 p.V433M variant, after stratification for different genotypes. Data extraction from published primary studies was possible for 24 articles.…”
Section: Resultsmentioning
confidence: 99%
“…Data extraction from published primary studies was possible for 24 articles. 5,6,15,1725,2732,3537,39,41,42 Data from one article34 were obtained from a published meta-analysis. 43 …”
Section: Resultsmentioning
confidence: 99%
“…Kringen et al [14] found that 32% of the variability in warfarin dose requirements among myocardial infarction patients could be explained by the VKORC1 and CYP2C9 polymorphisms.…”
Section: Discussionmentioning
confidence: 99%